PERAMALAN GENRE FILM TERPOPULER BERDASARKAN DATASET MYMOVIE MENGGUNAKAN METODE AUTOREGRESSIVE INTEGRATED MOVING AVERAGE (ARIMA) - Asrul; Witanti, Wina; Umbara, Fajri Rakhmat (Universitas Majalengka, 2023)
At this time the film industry is experiencing very rapid progress, this is because extraordinary technological developments have had a major influence on the film industry. Successful films tend to have a large audience. To find out why the audience likes a film, there are several variables that must be considered, one of which is the genre of the film. This research was conducted to predict what film genres the audience is most interested in. To predict the genre of this film using the autoregressive integrated moving average (arima) method. The autoregressive integrated moving average (arima) method or commonly known as the Box-Jenkins method is a method used to make precise and accurate short-term forecasts, compared to long-term forecasts which usually tend to be flat (flat/constant). From this research a prediction of the popularity or number of viewers of each film genre will be generated which can be used as a reference to find out what genre of film the audience is interested in. So that film production companies can adjust film releases according to their interests. audience, in order to gain greater profits.